Peran Organisasi Maritim Internasional (International Maritime Organization) Melalui Konvensi Di Bidang Kemaritiman Dalam Lalulintas Perdagangan Internasional Di Wilayah Perairan Indonesia - FX.Tetuko Zlatoper Sagala (Program Magister Ilmu Hukum Universitas Pancasila, 2021)
The sea is the widest part of the entire territory of Indonesia which has an important meaningand role not only as a unifier but also as a means of inter-island trade traffic. The geographicallocation of Indonesia, which is located between the continents of Asia and Australia andbetween the Indian and Pacific Oceans, has an important meaning in the economy, especiallyin international trade traffic and places Indonesia at the crossroads of world trade traffic. Withthis position, Indonesia has become a crossing point for world economic activities, betweenthe trade of industrialized countries and countries in Asia, Africa and Europe. This situation isnot only profitable but also has the potential to cause various legal problems not only relatedto jurisdiction but also other problems related to trading activities themselves. The InternationalMaritime Organization (IMO) is one of the international organizations that has an importantand strategic role in the shipping sector related to aspects of shipping safety and security.Trade between countries by sea - including through Indonesian territorial waters - is animportant part regulated in international agreements. The agreement established by theInternational Maritime Organization (IMO) greatly influences the provisions in the maritimesector and international trade shipping traffic and is a provision that must be adhered to andimplemented by all member countries